Empathy and Recognition - Donise, Anna (Itinerari, 2023)
The concept of “recognition” is traditionally linked to the ethical and social dimension of the human being. The paper proposes a different history of this concept, linking it to the sphere of knowledge. The story starts from Kant’s Critique of Judgement, in particular from the aesthetic judgement, and finds a fundamental stage in the reflection of the Munich philosopher and psychologist Theodor Lipps. For Lipps, the capacity to recognise (objects or other subjects) is closely intertwined with and dependent on the emotional dimension and on our empathic capacity (Einfühlung). Empathic recognition is a way of knowing the world, although it is constantly exposed to misunderstandings and mistakes that can lead to misinterpretation and misrecognition of objects and other subjects. In conclusion, the text argues for the need to distinguish between empathic-cognitive recognition, which recognises the characteristics of the “object” in question, and the recognition of the (ethical, aesthetic or social) value that this “object” is intended to have.